Global longitudinal strain in heart failure with reduced ejection fraction: Prognostic relevance across disease severity as assessed by automated cluster analysis. (1st June 2021) - Carluccio, Erberto; Pugliese, Nicola Riccardo; Biagioli, Paolo; Zuchi, Cinzia; Lauciello, Rosanna; Mengoni, Anna; D'Agostino, Andreina; Galeotti, Gian Giacomo; Dini, Frank Lloyd; Ambrosio, Giuseppe
Abstract: Background: Ejection fraction (EF) is still widely used to categorize heart failure (HF) patients but has limitations. Global longitudinal strain (GLS) has emerged as a new prognosticator in HF, independent of EF. Aim: We investigated the incremental predictive benefit of GLS over different risk profiles as identified by automated cluster analysis of simple echocardiographic parameters. Methods and results: In 797 HFrEF patients (age 66 ± 12y; mean EF 30 ± 7%), unsupervised cluster analysis of 10 routine echocardiographic variables (without GLS) was performed. Median follow-up was 37 months. End-point was all-cause mortality. Association between risk profiles, GLS, and mortality was assessed by Cox proportional-hazard modeling with interaction term. Cluster analysis allocated patients to 3 different risk phenogroups (PG): PG-1 (mild diastolic dysfunction [DD], moderate systolic dysfunction, no pulmonary hypertension, normal right ventricular [RV] function); PG-2 (moderate DD, mild pulmonary hypertension, normal RV function); PG-3 (severe DD, advanced systolic dysfunction, pulmonary hypertension, RV dysfunction). Compared to PG-1, PG-2 and PG-3 showed increased adjusted-hazard ratio (1.71; 95% CI:1.05–2.77, P  = 0.30; and 2.58; 95% CI:1.50–4.44, P  < 0.001, respectively). GLS was independently associated with outcome in the whole population (adjusted-HR: 1.11; 95% CI: 1.05–1.17, P  = 0.001); however, profile membership modified the relationship between GLS and outcome which was no longer significant in PG-3 (P for interaction = 0.003). Conclusions: Within HFrEF populations, clustering of routine echocardiography parameters can automatically identify patients with different risk profiles; further assessment by GLS may be useful for patients with not advanced disease. Highlights: HFrEF patients are extremely heterogeneous regarding etiology, clinical manifestations, and natural history. Cluster analysis allows identification of "echocardiographic phenogroups" with considerably different disease severity. The prognostic role of Global Longitudinal Strain varies across HF disease severity being not significant in advanced stage.